Kualitas Produk dan Harga dalam Mempengaruhi Minat Beli Konsumen - DYAN ARINTOWATI; Anggun Dwi Maretha (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
Technological developments and the increasingly modern era of globalization are currently driving the times and lifestyles of an increasingly modern society which has led to the development of increasingly varied and complex consumer needs. So this research is entitled